2017
DOI: 10.1177/1759720x17712695
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of intra-articular therapies in osteoarthritis: a literature review

Abstract: Osteoarthritis is a painful, chronic disease with widespread burden on patients, communities, health and social care systems. Conservative therapies, such as nonpharmacological interventions, systemic drug treatment and intra-articular therapies are used before resorting to surgery; nonetheless, disease control often remains inadequate. Recent advances in osteoarthritis management have aimed to provide greater variety of treatment options. Here, we summarize a targeted literature review evaluating efficacy and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
115
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(120 citation statements)
references
References 73 publications
(154 reference statements)
0
115
0
5
Order By: Relevance
“…Ozone IA seems to have a therapeutic effect similar to the IA application of corticosteroids in terms of duration. In patients with knee OA, it has been observed that corticosteroids decrease pain in the short term (1 month); however, some disadvantages are mentioned, such as the probable adverse effect on articular cartilage due to repeated exposure to corticosteroids . Although ozone therapy in addition to its antiinflammatory effects, could provide other benefits such as tissue oxygenation, increased antioxidant effects, cell metabolism activation, and stimulation of angiogenesis, effects that are not achieved with the application of corticosteroid IA.…”
Section: Discussionmentioning
confidence: 99%
“…Ozone IA seems to have a therapeutic effect similar to the IA application of corticosteroids in terms of duration. In patients with knee OA, it has been observed that corticosteroids decrease pain in the short term (1 month); however, some disadvantages are mentioned, such as the probable adverse effect on articular cartilage due to repeated exposure to corticosteroids . Although ozone therapy in addition to its antiinflammatory effects, could provide other benefits such as tissue oxygenation, increased antioxidant effects, cell metabolism activation, and stimulation of angiogenesis, effects that are not achieved with the application of corticosteroid IA.…”
Section: Discussionmentioning
confidence: 99%
“…11(p1006) The mechanism of action of PRP can be linked to its release of numerous growth factors that encourage bone and tissue healing via activation of various signaling pathways. 6 PRP injections are considered a newer and more unconventional method of treatment. Currently, they remain investigational, and the United States Food and Drug Administration has yet to regulate PRP.…”
Section: Prp and Review Of Literaturementioning
confidence: 99%
“…9 Moreover, PRP cannot be stored or frozen and must be drawn immediately before each injection, which can lead to greater variability in PRP injection composition. 6 There remain inherent risks associated with intra-articular injections, including infection (approximately 1 in 3,000 injections). 12 There is also a 2% to 25% possibility of a postinjection flare or local inflammatory response that can last 2 to 3 days and range from mild to severe.…”
Section: Prp and Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…2 The rapid increase in the prevalence of this already common disease suggests that OA will have a growing impact on health care and public health systems in future. 3 Viscosupplementation is a novel safe and possibly effective form of local treatment for osteoarthritis. 4 It aims at supplying replacement hyaluronic acid into the joint space to return the elasticity and viscosity of synovial fluid to normal.…”
Section: Introductionmentioning
confidence: 99%